ABCC6 Gene Analysis in 20 Japanese Patients with Angioid Streaks Revealing Four Frequent and Two Novel Variants and Pseudodominant Inheritance. (20th August 2017) - Katagiri, Satoshi; Negishi, Yuya; Mizobuchi, Kei; Urashima, Mitsuyoshi; Nakano, Tadashi; Hayashi, Takaaki
Abstract : Purpose . To report the spectrum of ABCC6 variants in Japanese patients with angioid streaks (AS). Patients and Methods . This was a single-center cohort study. The medical records of 20 patients with AS from 18 unrelated Japanese families were retrospectively reviewed. Screening of the ABCC6 gene (exons 1 to 31) was performed using PCR-based Sanger sequencing. Results . Eight ABCC6 variants were identified as candidate disease-causing variants. These eight variants included five known variants (p.Q378X, p.R419Q, p.V848CfsX83, p.R1114C, and p.R1357W), one previously reported variant (p.N428S) of unknown significance, and two novel variants (c.1939C>T [p.H647Y] and c.3374C>T [p.S1125F]); the three latter variants were determined to be variants of significance. The following four variants were frequently identified: p.V848CfsX83 (14/40 alleles, 35.0%), p.Q378X (7/40 alleles, 17.5%), p.R1357W (6/40 alleles, 15.0%), and p.R419Q (4/40 alleles, 10.0%). The ABCC6 variants were identified in compound heterozygous or homozygous states in 13 of 18 probands. Two families showed a pseudodominant inheritance pattern. Pseudoxanthoma elasticum was seen in 15 of 17 patients (88.2%) who underwent dermatological examination. Conclusions . We identified disease-causing ABCC6 variants that were in homozygous or compound heterozygous states in 13 of 18 families (72.2%). Our results indicated that ABCC6 variants play a significant role in patients with AS in the Japanese population.